Stabilization policies in Latin America: Some lessons for the new decade - Clavijo, Sergio (Estudios Económicos de El Colegio de México, 1992)
The purpose of this paper is to review some stabilization and/or structural adjustment programs adopted in Latin America (Argentina, Bolivia, Brazil, Colombia) during the period 1984-1988. The program of Israel is also included because it represents an interesting case for comparison. As a result of the analysis, a model of combined policies (i.e. with orthodox and heterodox features) is proposed.